The Role of the Reading Terrace in Increasing Village Children's Reading Interest - Deswalantri Deswalantri; Irham Habibi Harahap; Andri Kurniawan; Berman Hutahaean; Arafik Syaif; A. Nururrochman Hidayatulloh (AL-ISHLAH: Jurnal Pendidikan, 2023)
Books and libraries play an essential role in the democratization of information, even in the dissemination of knowledge, especially for today's children and youth who are more familiar with mobile phones than reading books. This paper aimed to investigate the role of the reading terrace in increasing village children’s reading interest. This study used a qualitative descriptive approach using the participatory action research method to determine the role of reading terraces in increasing children's interest in Balingka Village. This research data collection technique used observation, interviews, and documentation.  Data analysis techniques used the Miles and Huberman models in this study. The results of this study show that the availability of terrace facilities can influence the reading interest of Balingka children to be more effective and optimal for carrying out activities related to sustainable reading.